Assessing the Modern Multi‐Decadal Scale Aridification Over the Northern China From a Historical Perspective. Issue 3 (3rd February 2022) - Qin, Yanmin; Ning, Liang; Li, Longhui; Liu, Zhengyu; Liu, Jian; Yan, Mi; Chen, Kefan; Xue, Jiao; Wang, Liulin; Li, Chuxin
Abstract: Northern China (35°–50°N; 105°–125°E) has experienced a multidecadal aridification since 1950s, which was mainly manifested by multi‐decadal scale decreases of regional precipitation and soil moisture, and brought severe influences on societal and economic developments. However, the position of this aridification among the historical aridification events over northern China during the last millennium has not been fully assessed. Furthermore, the contributions from anthropogenic forcings, natural forcings, and internal variability on this aridification have not been quantitatively differentiated. In this study, observations, proxy reconstructions, and model simulations from community Earth system model last millennium ensemble archive were used to assess this aridification from a historical perspective, and differentiate the contributions from different forcings and internal variability. It was found that duration and magnitude of this aridification are more prominent than most of aridifications during the last millennium. The comparisons between control experiment and sensitivity experiments show that the external forcings, especially anthropogenic forcings, result in a significant larger aridification rate than other historical aridifications. Only combined impacts from internal variability (i.e., Pacific Decadal oscillation, PDO and Atlantic Multidecadal oscillation (AMO)) and anthropogenic forcings (e.g., greenhouses gas emission, anthropogenic aerosol emission, and land use cover changes) can result in such a severer aridification than historical aridifications. The results also confirm that the phase shifts of PDO and AMO trigger this aridification over the northern China, and, whether external forcings contribute to these phase shifts were also discussed. Key Points: Duration and magnitude of the current aridification are more prominent than most of historical aridifications during the last millennium Anthropogenic forcings result in a significant larger aridification rate than other historical aridifications Only combined impacts from internal variability and anthropogenic forcings can result in such a severer aridification